Insights into the molecular changes of adipocyte dedifferentiation and its future research opportunities - Mingheng Xue; Yunjun Liao; Wenqing Jiang (Journal of Lipid Research)
Recent studies have challenged the traditional belief that mature fat cells are irreversibly differentiated and revealed they can dedifferentiate into fibroblast-like cells known as dedifferentiated fat (DFAT) cells. Resembling pluripotent stem cells, DFAT cells hold great potential as a cell source for stem cell therapy. However, there is limited understanding of the specific changes that occur following adipocyte dedifferentiation and the detailed regulation of this process. This review explores the epigenetic, genetic, and phenotypic alterations associated with DFAT cell dedifferentiation, identifies potential targets for clinical regulation and discusses the current applications and challenges in the field of DFAT cell research.